Unseen Health and Social Challenges Among Residential Madrasah Students in Pakistan: A Cross-Sectional Study - Zubairuddin Quershi, Khalida Naz, Najeeb Memon, Ziauddin Quershi, Fatima Soomro, Farah Sheikh (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Madrasahs are Basic Islamic teaching schools and more often residential Islamic educational institutions that provide religious and basic formal education; however, the health and social conditions of students residing in these settings remain underexplored. Students may experience multiple health and psychosocial challenges, many of which are often underreported. Methodology: An institution-based cross-sectional study was conducted from January to March 2021 among 271 male students aged 13–19 years residing in a residential Madrasah in Hyderabad Sindh, Pakistan. Participants were selected through convenience sampling. Data were collected using a structured, pretested questionnaire assessing socio-demographic characteristics, Common health problems, social issues, and satisfaction levels. Data were analyzed using SPSS version 26.0. Descriptive statistics were presented as frequencies, percentages, and mean ± standard deviation. Associations between categorical variables were assessed using the chi-square test, with p < 0.05 considered statistically significant. Results: The mean age of participants was 17.7 ± 1.7 years. A high prevalence of health problems was observed, with only 6.64% reporting no illness and 20.30% experiencing multiple conditions. Approximately 50.55% of participants were satisfied with treatment received during illness. Satisfaction with food provided during illness was significantly associated with willingness to continue residing in the Madrasah (p < 0.001). Most participants (96.70%) reported engagement in sports activities. Conclusion: Despite adequate basic facilities, a considerable burden of health and social challenges persists among residential Madrasah students. Strengthening healthcare access, improving nutritional quality, and addressing psychosocial issues are essential to enhance student well-being. Keywords: Madrasah, Public health, Student health, Social issues, Satisfaction, Pakistan